A Perspective of Moral Theology on the Problem of Tissue Donation and Organ Transplantation - Olejnik, Stanisław (Studia Theologica Varsaviensia, 2020)
e main objective of the present article was to show what is the crux of the moral problem of transplanting human organs and how it should be resolved from the point of view of Christian morality. e issue posed by contemporary medicine reveals several aspects, therefore it cannot be resolved too hastily. e formulation of the general position on the fairness of transplantation required consideration of several specific issues implied by the general view of the phenomenon under discussion. Considering the situation of the donor, from whom the organ to be transplanted to someone else is taken, leads to the conclusion that retrieving the organ from the body of a deceased person cannot be regarded as impious or immoral. Similarly donation of one’s organ, whose transplantation is not necessary to maintain someone else’s life, should also be considered as morally correct. In the case of the donation of an organ necessary for maintaining the life of the donor, one should regard the act as morally condemnable, mainly because of the cooperation of the recipient with doctors, which aims at inflicting death on an innocent person. In certain specific situations, the donation of one healthy organs (from a pair), which is necessary to maintain the life of another person may turn out to be an obligation dictated by family love or the love of the fatherland. e greatest number of reservations and difficulties in the field of organ transplantation concern the issue of the recognition of death, especially in connection with the successes of resuscitation. One should bear in mind the ambiguity of death criteria in the ongoing discussions, from tests of death in a biological sense, through clinical death, ending with the recognition of the death of the brain. Despite the existing discrepancies in opinions, it is possible to declare the death of someone with full responsibility at a time when there is still the possibility of harvesting an organ from that person and transferring it to someone else. A judgement of this type is not and cannot be issued with absolute certainty. For the goals set in a given situation, it is completely sufficient and can fully justify undertaking transplantation activities. Conscientious consideration of the discussed case allowed the author of present article to conclude that the possible admission of the possibility of death in a given case cannot be identified with the deliberate act of taking someone’s life. e final conclusion of this key part of the investigation turned out to favor organ transplantation in the sense that it does not have to involve the accelerating the death of the donor. Practical difficulties with regard to organ transplantation, connected in particular with the need to establish specific preferences as to the selection of organ recipients on both a macro and micro ethical scale, are not sufficient arguments which could make us firmly reject their implementation. ey can be, however, overcome under certain conditions. ey are not, in any case, a decisive argument in favor of rejection of organ transplants in general. Also, possible abuses cannot be regarded as such an argument. It must be admitted that their occurrence is possible, and may pose a serious threat in this regard. Nevertheless, cases of abuse can accompany and indeed they do accompany all human activities, even the most noble in moral terms. In the face of the possibility of abuse, in the discussed area of medical activities, associated with a special kind of risk, it is necessary to appeal to doctors that they should maintain a great sense of responsibility and a noble moral attitude.